y = 388
x = 137
Multiply the second equation by 4 to give you 4x + 4y = 2100
Subtract this from the first equation to give you 2y = 776 and halve both sides to give you y = 388
Substitute in the second equation to give you x + 388 = 525 and x is therefore = 137.
2007-05-30 10:45:28
·
answer #1
·
answered by Anonymous
·
0⤊
2⤋
Series of two equations.
4x+6y = 2876
x+ y = 525
--------------------
Mulitply both sides of the bottom by 4
4x + 6y = 2876
4 (x + y) = 4(525) ==> 4x+4y =2100
4x + 6y = 2876
- (4x + 4y) = 2100
--------------------------
2y = 776 ==> y=388
Plug the value for y into either of the first two equations, I'll pick x+y = 525
x + 388 = 525 ==> x = 137
Test on other equation (4x + 6y = 2876)
4(137) + 6 (388) ==> 548 + 2328 = 2876 (check)
2007-05-30 10:44:31
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
*Solve for "x" or "y" in either equation. Let's solve for "x" in the 2nd equation.
1) 4x + 6y = 2876
2) x + y = 525
First: isolate "x" on one side (left) - subtract "y" from both sides (when you move a term to the opposite side, always use the opposite sign).
x + y-y = 525-y
x = 525-y
Sec: replace/substitute "525-y" with "x" in the 1st equation.
4(525-y) + 6y=2876
4(525)+4(-y)+6y = 2876
2100-4y+6y = 2876
2100+2y = 2876 (*Subtract 2100 from both sides).
2100-2100+2y = 2876-2100
2y = 2876-2100
2y = 776 (*Divide both sides by 2).
2y/2 = 776/2
y = 776/2
y = 388
Third: replace 388 with "y" in the 2nd equation.
x + 388 = 525 (*Subtract 388 from both sides).
x + 388-388 = 525-388
x = 525-388
x = 137
Solution set: (137, 388)
2007-05-30 11:07:08
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
Using the second equation and solving for X we get:
x = 525-y
Substitute this value for x in the first equation:
4(525-y) +6y = 2876
Multiply the terms getting:
2100 -4y +6y = 2876
Collect terms:
2100 +2y = 2876
Subtract 2100 from both sides getting:
2y = 776
Divide both sides by 2:
y = 388
Using the second equation:
x = 525 - 388 or
x = 137
Substitute the two values back into the equations as a check...
2007-05-30 10:42:26
·
answer #4
·
answered by BAM55 4
·
0⤊
0⤋
eqn#2 x= -y+525 (3)
sub in eq#1 4(-y+525) +6y =2876
2y+2100 = 2876
2y = 776
y = 388
sub in eqn#3 x= -388+525
x= 137
2007-05-30 10:40:32
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
4x + 6y = 2876
x + y = 525 | Origional Problem
4x+6y = 2876
-4x - 4y = -2100 | Multiplied bottom equation by negative 4
2y = 776 | Added equations together.
y = 388
x + (388) = 525 | Pluged y into origional equation
x = 137
2007-05-30 10:39:34
·
answer #6
·
answered by chess19902000 2
·
0⤊
0⤋
4x + 6y = 2,876
x + y = 525
4x + 4y = 2,100
2y = 776
y = 388
x = 525 - 388 = 137
2007-05-30 10:42:29
·
answer #7
·
answered by Helmut 7
·
0⤊
0⤋